2019
DOI: 10.1523/jneurosci.0966-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nociceptor Toll-like Receptor 4 (TLR4) in Opioid-Induced Hyperalgesia and Hyperalgesic Priming

Abstract: In addition to analgesia, opioids produce opioid-induced hyperalgesia (OIH) and neuroplasticity characterized by prolongation of inflammatory-mediator-induced hyperalgesia (hyperalgesic priming). We evaluated the hypothesis that hyperalgesia and priming induced by opioids are mediated by similar nociceptor mechanisms. In male rats, we first evaluated the role of nociceptor Toll-like receptor 4 (TLR4) in OIH and priming induced by systemic low-dose morphine (LDM, 0.03 mg/kg). Intrathecal oligodeoxynucleotide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 80 publications
10
70
0
Order By: Relevance
“…52,59,60 Rats were placed in cylindrical acrylic restrainers, with lateral ports that allowed access to the hind paw for nociceptive threshold testing. 9 They were acclimatized to the testing procedure prior to experimental manipulations. Mechanical nociceptive threshold is defined as the force in grams at which a rat withdrew its paw; and baseline threshold was defined as the mean of three readings taken before injection of test agents.…”
Section: Measuring Nociceptive Thresholdmentioning
confidence: 99%
“…52,59,60 Rats were placed in cylindrical acrylic restrainers, with lateral ports that allowed access to the hind paw for nociceptive threshold testing. 9 They were acclimatized to the testing procedure prior to experimental manipulations. Mechanical nociceptive threshold is defined as the force in grams at which a rat withdrew its paw; and baseline threshold was defined as the mean of three readings taken before injection of test agents.…”
Section: Measuring Nociceptive Thresholdmentioning
confidence: 99%
“…11,12 Recent studies have found that PKCε is also involved in the process of pain transition. [13][14][15][16] PKCε inhibitors can effectively prevent the occurrence of pain transition and modulate the long-term and severe chronic pain caused by this process, which is clearly separate from tissue damage. 14,17,18 However, the upstream pathway that is involved in pain transition remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that depending on the opioid used, and its dose and route of administration, opioids are capable of inducing acute hyperalgesia, even after a single administration (Araldi et al, 2015(Araldi et al, , 2018b(Araldi et al, ,c, 2019Ferrari et al, 2019). In particular, clinically used -opioid receptor (MOR) agonists, fentanyl (Araldi et al, 2018c) and morphine (Araldi et al, 2019;Ferrari et al, 2019), as well as the highly selective MOR agonist, DAMGO (Araldi et al, 2015(Araldi et al, , 2017(Araldi et al, , 2018a, produce OIH and hyperalgesic priming, a form of nociceptor neuroplasticity characterized by a persistent increase in responsivity of nociceptors to proalgesic mediators (Ferrari et al, 2010;Joseph and Levine, 2010b;Alvarez et al, 2014;Araldi et al, 2015;Khomula et al, 2017). Recent evidence has implicated a role of the action of MOR agonists on primary afferent nociceptors in OIH (Corder et al, 2017).…”
Section: Introductionmentioning
confidence: 99%